The Influence of Product Quality and Price on Purchase Decisions (A Study of Students at STIE Stan Indonesia Mandiri Who Use Shopee). - Rahmawati, Neng Riny; Rohmat, Deni (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2026)
This study aims to examine and analyze the influence of product quality and price on purchasing decisions among students at STIE STAN Indonesia Mandiri who use the Shopee application. This study addresses a research gap regarding persistent inconsistencies in previous findings on the significance of price effects, as well as a notable scarcity of research specifically examining these factors among this targeted student population. This study employs a quantitative method. The population consisted of 610 students at STIE STAN Indonesia Mandiri, from which a sample of 86 respondents was selected. The statistical tests utilized include the simultaneous test (F-test), partial test (t-test), and determination coefficient. The results indicate that product quality has a positive and significant influence on purchasing decisions with a t-value of 2.824 and a significance level of 0.006. Price also demonstrates a positive and significant effect on purchasing decisions with a t-value of 4.979 and a significance level of 0.000. Simultaneously, both product quality and price have a positive and significant effect on purchasing decisions, evidenced by a significance level of 0.000. The coefficient of determination (R²) is 0.573, meaning that 57.3% of the variation in purchasing decisions can be explained by product quality and price, while the remaining 42.7% is attributed to other variables not included in this study. In conclusion, purchasing decisions among STIE STAN Indonesia Mandiri students fall into the good (high) category and are significantly influenced by both product quality and price.